Pengaruh Model Pembelajaran Kooperatif Tipe Make a Match terhadap Hasil Belajar Pendidikan Pancasila Siswa Kelas V SD Negeri Rayung II - Yulia Nur Azizah; Ana Naimatul Jannah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The learning model is a conceptual framework that describes a systematic procedure in organizing learning experiences to achieve learning goals. This study aims to determine the influence of the make a match type cooperative learning model on the learning outcomes of Pancasila education for grade V students of SD Negeri Rayung II. This research method is quantitative with a pre-experimental design of one group pretest posttest design. All students in grade V of SD Negeri Rayung II for the 2023/2024 school year were used as the population in this study. Sampling uses nonprobability sampling techniques with total sample types. The research sample was 26 students. The data collection technique in this study uses test questions and observation sheets. The results of the study prove that the make a match type cooperative learning model can have an influence on student learning outcomes. The make a match type cooperative learning model was implemented well according to its syntax, so that it affected the results of the t paired sample t-test test with a calculated value of 16.223 ≥ 1.708 so that Ha was accepted, namely there was a difference in the value of learning outcomes between the pretest and the posttest using the make a match type cooperative learning model. This shows that there is an influence of the make a match type cooperative learning model on the learning outcomes of Pancasila education for grade V students of SD Negeri Rayung II.